N- and L-Type Voltage-Dependent Ca2+ Channels Contribute to the Generation of After-Discharges in the Spinal Ventral Root After Cessation of Noxious Mechanical Stimulation - Shohei Yamamoto; Mitsuo Tanabe; Hideki Ono (Elsevier, 2012)
Voltage-dependent Ca2+ channels (VDCCs) play a crucial role in the spinal pain transduction. We previously reported that nociceptive mechanical stimuli to the rat hindpaw evoked two types of ventral root discharges that increased during stimulation (during-discharges) and after cessation of stimulation (after-discharges). To explore the involvement of VDCCs in these ventral root discharges, several VDCC blockers were applied directly to the surface of the spinal cord. Spinalized rats were laminectomized. The fifth lumbar ventral root was sectioned and used for multi-unit efferent discharges recording. An agar pool was constructed on the first lumbar vertebra for drug application. Ethosuximide (a T-type VDCC blocker) had no effect on ventral root discharges. ω-Conotoxin GVIA (an N-type VDCC blocker) preferentially suppressed after-discharges. ω-Agatoxin IVA (a P/Q-type VDCC blocker), diltiazem, and verapamil (L-type VDCC blockers) nonselectively depressed both during- and after-discharges. The more selective L-type VDCC blocker nicardipine depressed only after-discharges and the depression was exhibited when nicardipine was microinjected into the dorsal horn, but not into the ventral horn. These findings suggested that N- and L-type VDCCs in the dorsal horn were involved in the generation of afterdischarges and these blockers might be useful for treatment of persistent pain that involves the spinal pathway. Keywords:: after-discharges, dorsal horn, L-type voltage-dependent Ca2+ channel, N-type voltage-dependent Ca2+ channel, spinal cord